The Design of 3D Animation Media to Reflect Youth Defense Mechanisms Against Bullying - แซ่ฮั่น, ฝุ่นทิพย์; ดีเจริญชิตพงศ์, จิรวิญญ์; เขื่อนแก้ว, ปรานต์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to develop a 3D animation media presenting the issue of bullying among youth through symbolic storytelling. The objectives were: 1) to design and develop a 3D animation reflecting youth defense mechanisms against bullying; 2) to convey the perspectives and psychological states of children who experience emotional violence from bullying through symbolic storytelling; and 3) to evaluate youth satisfaction with the developed animation.           The results showed that the content quality evaluated by content experts had a mean score of 4.70 (highest level), while the media quality evaluated by media experts had a mean score of 4.33 (high level). The satisfaction of Grade 9 students from Thainiyomsongkroh School who watched the animation had a mean score of 4.32, indicating a high level of satisfaction.